Secondary Precursor T-Cell Lymphoblastic Lymphoma Following Precursor B-cell Acute Lymphoblastic Leukemia: A Case Report and Review of the Literature (Journal of Cancer Research Updates, 2014)
Although relapse of lymphoma/leukemia is not uncommon, sequential development of a second lymphoma/leukemia of a different cell lineage is rare. We report the case of a 3-year-old girl who initially presented with precursor B-cell acute lymphoblastic leukemia (B-ALL), characterized by a cryptic t(12;21) with associated ETV6/RUNX1 fusion, an 11q (MLL) deletion, and a balanced inv(2)(q31q37). She was successfully treated but five years later developedthymicprecursor T-cell lymphoblastic lymphoma (T-LBL) expressing a completely different phenotypic profile. Fluorescence in situ hybridization testing identified a MLL rearrangement but indicated no ETV6/RUNX1 fusion. Although the marrow was uninvolved, aspirates evaluated by chromosome studies revealed the same inv(2q), suggesting a constitutional abnormality distinct from the somatic alterations associated with her B-ALL and T-LBL. This raisesthe possibilityof a potential tumor suppressor gene or proto-oncogene residing in the region of the inversion breakpoints which could contribute to predisposition to the development of lymphoblastic leukemias/lymphomas. While secondary leukemia may emerge as a therapy-related process and the presence of an MLL rearrangement in the T-LBL represents an interesting abnormality in this regard,athymicpresentation would be exceedingly unusual. To our knowledge, this is the first reported case of B-ALL followed by an apparently genetically unrelatedT-LBL.